Teologi Belaskasih Allah dalam Puisi “Sepotong Hati Di Angkringan” (2022) Karya Joko Pinurbo - Prihartanti, Marcellina; Andalas, Patricius Mutiara (Fakultas Teologi, Universitas Sanata Dharma, 2024)
Every human being longs for intimacy with God, receiving His merciful grace. Many of Joko Pinurbo's poems raise the theme of the closeness of human relations. One of Pinurbo's articulate poems voicing social compassion is entitled